2017
DOI: 10.4103/0972-9941.181760
|View full text |Cite
|
Sign up to set email alerts
|

An unusual approach for the treatment of oesophageal perforation: Laparoscopic-endoscopic cooperative surgery

Abstract: Boerhaave syndrome describes a transmural oesophageal rupture that develops following a spontaneous, sudden intraluminal pressure increase (i.e. vomiting, cough). It has a high rate of mortality and morbidity because of its proximity to the mediastinum and pleura. Perforation localisation and treatment initiation time affect the morbidity and mortality. In this article, we aim to present our successful laparoscopic-endoscopic cooperative surgery in a 59-year-old female who was referred to our clinic with a dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 24 publications
0
1
0
1
Order By: Relevance
“…Vogel et al reported an overall survival rate of 96% in 47 patients with esophageal perforation and emphasized that the aggressive treatment of sepsis and pleural fluid collection can prevent the need for major surgery [19]. In addition, the efficiency of self-expanding esophageal stents, such as the HANAROSTENT and SX-ELLA esophageal stents (ELLA-CS, Hradec Kralove, Czech Republic), in blocking the site of leakage has been reported, suggesting that they might help control sepsis and reduce mortality and morbidity [9, 21, 22]. Dasari et al reported a technical success rate of stent placement of 91.4% and a healing rate of 81% [9].…”
Section: Discussionmentioning
confidence: 99%
“…Vogel et al reported an overall survival rate of 96% in 47 patients with esophageal perforation and emphasized that the aggressive treatment of sepsis and pleural fluid collection can prevent the need for major surgery [19]. In addition, the efficiency of self-expanding esophageal stents, such as the HANAROSTENT and SX-ELLA esophageal stents (ELLA-CS, Hradec Kralove, Czech Republic), in blocking the site of leakage has been reported, suggesting that they might help control sepsis and reduce mortality and morbidity [9, 21, 22]. Dasari et al reported a technical success rate of stent placement of 91.4% and a healing rate of 81% [9].…”
Section: Discussionmentioning
confidence: 99%
“…В опубликованных клинических наблюдениях последних десяти лет эндоскопические операции выполнены 7 пациентам (24,1%): стентирование -n=3 [8,25,32], клипирование -n=1 [42], эндоскопическое наложение заплаты из полигликоевой кислоты -n=2 [36] и T-образное дренирование разрыва -n=1 [30].…”
Section: результаты исследования и их обсуждениеunclassified